Dispositivo para auxiliar na recuperação da marcha - Taguti, Érika Mari [UNESP] (2016)
The rehabilitation of gait in patients, who are unable to produce the coordinated movements due to of neurological affections or musculoskeletal affections, is a difficult and a slow task. Restoring ambulation requires significant technique and support from the physiotherapist to guide and assist the patient. So, the methods of the rehabilitation have been developed with the aid of the engineering and the main device used the partial weight support (PWS) which consists in suspending the individual over a treadmill. Through this type of locomotor training with PWS, better results can be achieved as the increase of the ability to travel greater distances, lower energy expenditure and training with higher speeds when compared to conventional one. Thus, this work aims to obtain a prototype design of an PWS device whose main components are a metal structure in which the patient is suspended, the steel cable and the weight control device. Project requirements have been defined to have a safety device, an weight control and an easy patient / support placement. Through these considerations, it was possible to obtain a simple mechanical device, but there are still things to study as the actual budget and the complete assembly, although the project has been designed to have low cost